Economic analysis of expediency of the introducing of information security systems cellular networks 4G - Козлюк, Ірина Олексіївна; Одарченко, Роман Сергійович; Ткаченко, Вадим Валерійович; Марченко, Олександр Вікторович (Ukrainian Information Security Research Journal, 2012)
A model evaluation of the economic effectiveness of the protection system of fourth generation (4G) cellular networks is considered. The mathematical apparatus to assessfeasibility of introducing the 4G network security and an algorithm for evaluation of their economic efficiency are given.